Love and Liberation – Autobiographical Writings of the Tibetan Buddhist Visionary Sera Khandro, by Sarah Jacoby. - Yener, Güzin A. (Buddhist Studies Review, 2017)
Love and Liberation – Autobiographical Writings of the Tibetan Buddhist Visionary Sera Khandro, by Sarah Jacoby. Columbia University Press, 2014. 456pp, 19 b&w photographs. Pb. £30. ISBN-13: 9780231147699